Differential neuroprotective potential of CRMP2 peptide aptamers conjugated to cationic, hydrophobic, and amphipathic cell penetrating peptides - Moutal, Aubin; François-Moutal, Liberty; Brittain, Joel M.; Khanna, May; Khanna, Rajesh (Frontiers in Cellular Neuroscience, 2015)
The microtubule-associated axonal specification collapsin response mediator protein 2 (CRMP2) is a novel target for neuroprotection. A CRMP2 peptide (TAT-CBD3) conjugated to the HIV transactivator of transcription (TAT) protein’s cationic cell penetrating peptide motif (CPP) protected neurons in the face of toxic levels of Ca2+ influx leaked in via N-methyl-D-aspartate receptor (NMDAR) hyperactivation. Here we tested whether replacing the hydrophilic TAT motif with alternative cationic (nona-arginine (R9)), hydrophobic (membrane transport sequence (MTS) of k-fibroblast growth factor) or amphipathic (model amphipathic peptide (MAP)) CPPs could be superior to the neuroprotection bestowed by TAT-CBD3. In giant plasma membrane vesicles (GPMVs) derived from cortical neurons, the peptides translocated across plasma membranes with similar efficiencies. Cortical neurons, acutely treated with peptides prior to a toxic glutamate challenge, demonstrated enhanced efflux of R9-CBD3 compared to others. R9-CBD3 inhibited N-methyl-D-aspartate (NMDA)-evoked Ca2+ influx to a similar extent as TAT-CBD3 while MTS-CBD3 was ineffective which correlated with the ability of R9- and TAT-CBD3, but not MTS-CBD3, to block NMDAR interaction with CRMP2. Unrestricted Ca2+ influx through NMDARs leading to delayed calcium dysregulation and neuronal cell death was blocked by all peptides but MAP-CBD3. When applied acutely for 10 minutes, R9-CBD3 was more effective than TAT-CBD3 at neuroprotection while MTS- and MAP-CBD3 were ineffective. In contrast, long-term (> 24 hours) treatment with MTS-CBD3 conferred neuroprotection where TAT-CBD3 failed. Neither peptide altered surface trafficking of NMDARs. Neuroprotection conferred by MTS-CBD3 peptide is likely due to its increased uptake coupled with decreased efflux when compared to TAT-CBD3. Overall, our results demonstrate that altering CPPs can bestow differential neuroprotective potential onto the CBD3 cargo.